The influence of online bamboo product marketing strategy on consumer buying interest - Hafizah Arinah; Muhammad Dimas; Iwan Risnasari; Evalina Herawati; Alisyah Madani; Wahyu Andayani (Global Forest Journal., 2026)
Compared with the large literature on generic e-commerce goods, research on how online marketing strategy shapes consumer interest in traditional non-timber forest products (NTFPs) is thin. Bamboo ulos bags illustrate the gap well: they combine everyday functionality with cultural and local wisdom, so consumers may not respond to their online marketing the same way they do to mass-market products. That is the question this study tests. The study examines the effect of online marketing strategy on purchase interest at Etnobambu Craft, an online store in North Sumatra, Indonesia that sells bamboo ulos bags. It uses an associative-descriptive design and covers the store's full population of 20 customers who bought a bag between August and September 2024, via census sampling. Data collection relied on a five-point Likert questionnaire adapted from established digital marketing mix and purchase intention indicators. The analysis was conducted using SPSS 25, which included several tests: the Pearson product-moment correlation test, Cronbach's alpha for reliability, the Kolmogorov-Smirnov normality test, and a simple linear regression model. From the data analysis, it is known that the online marketing strategy received an average score of 77.8 and a purchase interest score of 76.4, both in the "good" category. The results of the simple linear regression model analysis are significant from the marketing strategy to purchase interest (p = 0.000 < 0.05; Y = 38.200 + 1.000X). Therefore, social media promotions, discounts, and free shipping are the most important and beneficial strategies for forest product-based SMEs seeking to drive purchase interest in bamboo-based craft products through online marketing